Treated and untreated rock dust: Quartz content and physical characterization. Issue 11 (1st November 2016) - Soo, Jhy-Charm; Lee, Taekhee; Chisholm, William P.; Farcas, Daniel; Schwegler-Berry, Diane; Harper, Martin
ABSTRACT: Rock dusting is used to prevent secondary explosions in coal mines, but inhalation of rock dusts can be hazardous if the crystalline silica (e.g., quartz) content in the respirable fraction is high. The objective of this study is to assess the quartz content and physical characteristics of four selected rock dusts, consisting of limestone or marble in both treated (such as treatment with stearic acid or stearates) and untreated forms. Four selected rock dusts (an untreated and treated limestone and an untreated and treated marble) were aerosolized in an aerosol chamber. Respirable size-selective sampling was conducted along with particle size-segregated sampling using a Micro-Orifice Uniform Deposit Impactor. Fourier Transform Infrared spectroscopy and scanning electron microscopy with energy-dispersive X-ray (SEM-EDX) analyses were used to determine quartz mass and particle morphology, respectively. Quartz percentage in the respirable dust fraction of untreated and treated forms of the limestone dust was significantly higher than in bulk samples, but since the bulk percentage was low the enrichment factor would not have resulted in any major change to conclusions regarding the contribution of respirable rock dust to the overall airborne quartz concentration. The quartz percentage in the marble dust (untreated and treated) was very low and the respirable fractions showed no enrichment. The spectra from SEM-EDX analysis for all materials were predominantly from calcium carbonate, clay, and gypsum particles. No free quartz particles were observed. The four rock dusts used in this study are representative of those presented for use in rock dusting, but the conclusions may not be applicable to all available materials.